Characteristics of patients with COVID‐19 hospitalised in South Australia during the first wave of the pandemic. (13th December 2021) - Boyle, Justin; Sparks, Ross
Abstract: Objective: To describe the first wave of hospitalisations of patients testing positive for COVID‐19 in South Australia. Methods: Pathology test results for COVID‐19 between January and June 2020 were matched against state‐wide ED and inpatient data sets. Results: The impact of the first wave of COVID‐19 on South Australian hospitals was 440 unique patients with COVID‐19; median ED, hospital and ICU lengths of stay of 4.7 h, 9.8 days and 4.1 days, respectively; and a crude mortality rate of 0.23 deaths per 100 000 population (four deaths). Conclusion: The study sheds light on the characteristics of patients with COVID‐19 hospitalised in South Australia. Abstract : This short report sheds light on characteristics of patients with COVID‐19 hospitalised in South Australia. There is new knowledge regarding primary diagnoses assigned in hospital for patients who tested positive to COVID‐19.